Efectos del reacondicionamiento en la base de los brackets utilizando tres métodos de eliminación de resina - un estudio Cuasi-experimental de tipo antes y después. (2022)
Orthodontists have commonly been faced with the decision of what to do with brackets that have debonded, one of the alternatives is to recycle them, the methods used for this technique must completely remove the material without damaging the base of the bracket, to achieve this it is Various reconditioning methods have been developed. Therefore, the objective of this study is to compare the changes in the base of the bracket when using different reconditioning techniques in metal brackets from two different commercial houses; a sample of 60 upper and lower premolars will be taken where 3 groups of 20 teeth will be formed, each one of which will be cemented with prescription MBT slot 0.022x0.028 metal brackets, these will be reconditioned with micro-sandblasting, direct flamed and diamond bur 40 micron yellow halo superfine grit, subsequently, the effect or changes caused in the mesh of the support will be observed by means of optical microscopy, and the effectiveness of the removal of the remaining resin